Microfluidic Concentration Gradient for Toxicity Studies of Lung Carcinoma Cells. (2017) - Zaidon, Nuradawiyah; Mansor, Ahmad Fairuzabadi Mohd; Mak, Wing Cheung; Ismail, Ahmad Faris; Nordin, Anis Nurashikin
Abstract: Cancer is a serious global health problem, which resulted in 8.2 million deaths in 2012 alone. Amongst different types of cancer, lung cancer is the most lethal and contributes 19.4% of cancer deaths. Better disease-free cancer survival rates have been reported when surgery is followed by systemic chemotherapy. Efficient treatment can be achieved through personalized chemotherapy dosage whereby optimum treatment is given to kill the cancer the side effects are minimized. Here, we present a microfluidic concentration gradient device for toxicity studies on lung cancer cell lines (A549). Automated drug dilution is achieved by simply tuning the flow rate and geometries of the microfluidics network. Sets of tree-like-concentration-generators were designed to achieve constant flow rate at each outlet by optimizing the channel lengths. Serpentine structures were placed in the middle in the middle and at each outlet channel to the design to improve mixing along the channel. The lengths of middle and outlet channels are varied from 1.5 mm to 12 mm to obtain sufficient mixing of two fluid flows. Theoretically, correlations between hydraulic flow and electrical circuit equations analogy were applied to ease the microfluidic design process. Later, 3D (dimensional) simulations using computational fluid dynamic (CFD)-based simulator, i.e. Ansys FLUENT were performed by implementing species transport method prior to fabrication. The simulation process helps to demonstrate the effect of varying channel length on the velocity magnitude and the concentration of the microfluidic structure. In addition, the simulation results allows us predict the fluid flow velocity that showed constant velocity magnitude at each outlet. Wider range of dilution can be achieved, when a higher number of outlets are added in a microfluidic design. Polydimethylsiloxane (PDMS) microchannels were fabricated on glass slide widths of 200 μm and depths of 35 μm using soft-lithography technique[1] . The 3-outlet serpentine structure produced the best match between simulation and measurement results. The concentration profiles produce inside the channel is determined by the splitting ratio of the fluids at each branched and also depends on the number of the inlet and outlet in the tree-like network. The gradient generator will be attached to an array of cell culture chambers with sensors that were previously developed for toxicity studies of lung cancer (A549) cell lines is shown in the Fig. 2. Cells cultured in the sensor will begin to attach and spread on the surface of the electrodes, restricting current flows from the electrodes to the surrounding media. In a confluent (all surface covered with cells) cell layer, current must travel through the intercellular space of the cell-cell and also the tight gap of the cell-electrode pairs to reach surrounding media. The more adhered the cells are with each other and with the electrode, the lesser the amount of current that could travel out, thus increasing the overall impedance of the system. This leads to a good way of studying cell-cell and cell-electrode adhesion characteristics by using impedance measurement[2, 3] . When sensors are treated with Taxol, the cell index (CI) values of the cancer cells exhibit inconsistent trend with several peaks during the measurement (over 96 hours) as shown in Fig.1. This is due to the nature of cells that are mixed combinations of drug-sensitive cells and drug resistance cells. This work provides a promising solution for automated drug dilution in parallel toxicity studies. The use of microfluidics allows highly parallel, maximum testing with minimal reagents to obtain the optimum dosage.